Women's experiences of midwifery care immediately before and after caesarean section deliveries at a public Hospital in the Western Region of Ghana - Agani Afaya; Veronica Millicent Dzomeku; Elizabeth A. Baku; Richard Adongo Afaya; Mavis Ofori; Samuel Agyeibi; Frederick Boateng; Rosemond Ohwui Gamor; Elsie Gyasi-Kwofie; Prudence P. Mwini Nyaledzigbor (BMC, 2020)
Abstract Background Childbirth remains a uniquely multifaceted, mental-cognitive and a major life experience to women. It is composed of a variety of psycho social and emotional aspects and creates memories, sometimes bad experiences and unmet expectations which leaves the mother with lasting scars. Therefore, this study aimed at exploring post-caesarean section delivered mothers experiences of midwifery care in a public hospital in Ghana. Methods This descriptive exploratory qualitative research used an interpretative approach to explore mothers' experiences of midwifery care immediately before and after caesarean section (CS). The study employed a purposive sampling technique in recruiting 22 participants who had knowledge of the phenomenon under study. Data collection was guided by an interview guide, which involved face to face individual interviews and focus group discussion at the postnatal ward and clinic. All interviews were audio-recorded and lasted 30-40 min. Audio recordings were transcribed verbatim and inductive thematic data analysis employed. Results Four major themes emerged from the analysis of participants' transcripts: Support by Midwives (physical and psychological, and attitude towards patients' pain management); Protection of mothers (provision of privacy, confidentiality and physical environment); Provision of information/communication (before caesarean section, and before a minor task) and midwives' attitude (attitude towards delivery care). Conclusion Mothers delivered by caesarean section had varied experiences of midwifery care which were both positive and negative ones. Provision of psychological support and adequate pain management were positive experiences. The challenges experienced were related to provision of information, privacy, and physical support. Participants, who underwent emergency CS in particular, were dissatisfied with the provision of information concerning the surgical procedure. Provision of privacy and physical support were also issues of great concern. We therefore, recommend supportive and sensitive midwifery care particularly for mothers undergoing emergency CS. Documenting women's diverse experiences of midwifery care before and after CS delivery is important to healthcare providers, hospital managers and policy makers as the feedback garnered can be used to improve maternity services and inform decisions on midwifery care.